In vitro Activity of Repurposed Nitroxoline Against Clinically Isolated Mycobacteria Including Multidrug-Resistant Mycobacterium tuberculosis - Hoffmann, Ada Marie; Wolke, Martina; Rybniker, Jan; Plum, Georg; Fuchs, Frieder (Frontiers in Pharmacology, 2022)
Antimicrobial treatment options for mycobacterial infections are limited due to intrinsic resistance and the emergence of acquired resistance in Mycobacterium tuberculosis. Isolates resisting first- and second line drugs are raising concerns about untreatable infections and make the development of new therapeutic strategies more pressing. Nitroxoline is an old oral antimicrobial that is currently repurposed for the treatment of urinary tract infection (UTI). In this study, we report the in vitro activity of nitroxoline against 18 clinical isolates of M. tuberculosis complex (MTBC) (M. tuberculosis N = 16, M. bovis BCG N = 1, M. bovis sp. bovis N = 1). Since nitroxoline achieves high concentrations in the urinary tract, we included all MTBC-isolates from urinary samples sent to our laboratory between 2008 and 2021 (University Hospital of Cologne, Germany). Isolates from other sources (N = 7/18) were added for higher sample size and for inclusion of drug-resistant M. tuberculosis isolates (N = 4/18). Based on our clinical routine the fluorescence-based liquid media system BACTEC MGIT 960 was used for susceptibility testing of nitroxoline and mainstay antitubercular drugs. Nitroxoline yielded a MIC90 of 4 mg/L for MTBC. In all M. tuberculosis isolates nitroxoline MICs were at least two twofold dilutions below the current EUCAST susceptibility breakpoint of ≤16 mg/L (limited to E. coli and uncomplicated UTI). In vitro activity of nitroxoline can be considered excellent, even in multidrug-resistant isolates. Future studies with in vivo models should evaluate a potential role of nitroxoline in the treatment of tuberculosis in the era of drug resistance.